2000
DOI: 10.1068/p3060
|View full text |Cite
|
Sign up to set email alerts
|

Depth Discrimination from Shading under Diffuse Lighting

Abstract: The human visual system has a remarkable ability to interpret smooth patterns of light on a surface in terms of 3-D surface geometry. Classical studies of shape-from-shading perception have assumed that surface irradiance varies with the angle between the local surface normal and a collimated light source. This model holds, for example, on a sunny day. One common situation in which this model fails to hold, however, is under diffuse lighting such as on a cloudy day. Here we report on the first psychophysical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(107 citation statements)
references
References 24 publications
(27 reference statements)
4
102
0
Order By: Relevance
“…Instead it is necessary to take into account the gradient of blurriness, in order to compare the depth of two reference points. In contrast, when using Volumetric Halos and Depth Darkening, the viewer can assume dark-means-deep, as similarly observed also by Langer and Bülthoff [1999].…”
Section: Results Discussionmentioning
confidence: 79%
“…Instead it is necessary to take into account the gradient of blurriness, in order to compare the depth of two reference points. In contrast, when using Volumetric Halos and Depth Darkening, the viewer can assume dark-means-deep, as similarly observed also by Langer and Bülthoff [1999].…”
Section: Results Discussionmentioning
confidence: 79%
“…This approach is based on the idea of "dark-is-deep" which can be seen as one (of possibly several) components of human depth perception [Langer and Bülthoff 2000]. We demonstrate here that it can also be used to produce procedural, perceptually-plausible caustics, relying on two key insights.…”
Section: Depth Recoverymentioning
confidence: 99%
“…However, faces are not globally convex and it has been shown that occlusions of the illumination environment play an important role in human perception of 3D shape [103]. Prados et al [104] have shown how shading caused by occlusion under perfectly ambient illumination can be used to estimate 3D shape.…”
Section: Global Shadingmentioning
confidence: 99%
“…Estimation of 3D shape from ambient shading has received very little attention in comparison to the classical point source shape from shading problem. Langer and Bülthoff [103] showed the importance of ambient shading in human perception of shape. Langer and Zucker [70] were the first to study the problem from a computational perspective.…”
Section: Shape From Ambient Occlusionmentioning
confidence: 99%